PENGARUH PENCARIAN INFORMASI, PERSEPSI RISIKO TERHADAP KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN PADA E-COMMERCE BUKALAPAK DI KOTA PEKANBARU - Purba CR Lestari; Restuti Sri; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of information search, Perceived risk ontrust and purchasing decisions at E-Commerce Bukalapak in Pekanbaru City. Thepopulation of this study is the Bukalapak site in Pekanbaru. Data collection wascarried out using a questionnaire with a non-probability sampling technique anda sample of 100 people. This research method uses path analysis with the SPSS 20program. The results show that: 1) Information search influences trust inBukalapak e-Commerce in Pekanbaru City; 2) Perceived risk influences trust inBukalapak e-Commerce in Pekanbaru City; 3) Information search influencespurchasing decisions at Bukalapak e-Commerce in Pekanbaru City; 4) Perceivedrisk influences purchasing decisions at Bukalapak e-Commerce in PekanbaruCity. 5) Consumer trust influences purchasing decisions at e-CommerceBukalapak in Pekanbaru City. 6) Information search influences purchasingdecisions through trust in Bukalapak e-Commerce in Pekanbaru City. 7)Perceived risk influences purchasing decisions through trust in Bukalapak eCommerce in Pekanbaru City. Keywords: Information Search, Perceived Risk, Trust, Purchasing Decisions